COMPARISON OF OUTCOME BETWEENTRANSRADIALAND TRANSVENOUS PERCUTANEOUSANGIOPLASTY FOR STENOSEDHEMODIALYSIS ACCESS FISTULA - Hasan, Dr. Rakibul; Hossain, Dr. G M Mokbul; Mahmud, Dr. Mainul; Das, Dr. Debashish; Saha, Dr. Samaresh Chandra (The journal of contemporary issues in business and government, 2021)
Background: The outcomes of enhancing vascular access remain an ongoing challenge for vascular surgery. Mature fistulas have better longevity and require fewer interventions. The major obstacle to increasing fistula approach is the higher rate of failure due to the maturity of newly created fistulas. Hemodialysis access fistulas are the lifeline of an end stage renal disease patient on hemodialysis. With the raise in the rate of development of end stage renal disease, the creation of arteriovenous fistula has become the most frequent performing procedure in a vascular surgery outpatient department. Aim of The Study:The purpose of this study was to compare the early and long-term outcomes of trans venous and trans radial fistuloplasty in a single surgeon's practice and to provide information on treatment strategies for patients with end-stage renal disease .Material & Methods: This prospective study was carried out in vascular care center in Ibn Sina hospital, Dhanmondi, Dhaka, Bangladesh from 2017 to 2019. A total number of 50 patients who needed endovascular interventions for non-functioning fistula, were selected for the study. The inclusion criteria were thrombotic or fibrous stenosis of >50% of luminal area and flow volume <600ml/min on Doppler ultrasound study. The exclusion criteria were-primary failure of AV fistula, critical stenosis (>90% reduction in luminal diameter), long segment venous stenosis (>2.5cms), stenosis that were associated with the presence of a small or calcified or stenotic feeding artery due to progressive atherosclerosis . Results: The mean age of patients was 54.14±7.05 and 50.3±8.65 years. Male were 18(51.4%) & 17(48.6%) and female 9(60%) & 6(40%) in group A and group B. Three types of intervention offered (thrombolysis 6%, balloon dilatation 74% and stenting 20%). Follow up after 6 months, 80% fistula were functional and 20% non-functional. Conclusion: Conventional trans venous fistuloplasty, is an effective way of dealing with a non-functioning haemodialysis fistula. In the past, this technique was employed for maintaining access for hemodialysis. Transradial approach is relatively safer, as it has fewer chances of distal embolization. The identification of AV anastomosis is easier and the whole procedure can be performed safely with less fluoroscopic exposure.